Introducing N2-fixing trees (Acacia mangium) in eucalypt plantations rapidly modifies the pools of organic P and low molecular weight organic acids in tropical soils - Waithaisong, Kittima; Robin, Agnès; Mareschal, Louis; Bouillet, Jean-Pierre; Laclau, Jean-Paul [UNESP]; Deleporte, Philippe; Gonçalves, José Leonardo de Moraes; Harmand, Jean-Michel; Plassard, Claude (Elsevier, 2020)
Many studies have shown that introducing N2-fixing trees (e.g. Acacia mangium) in eucalypt plantations can increase soil N availability as a result of biological N2 fixation and faster N cycling. Some studies have also shown improved eucalypt P nutrition. However, the effects of N2-fixing trees on P cycling in tropical soils remain poorly understood and site-dependent. Our study aimed to assess the effects of planting A. mangium trees in areas managed over several decades with eucalypt plantations on soil organic P (Po) forms and low molecular weight organic acids (LMWOAs). Soil samples were collected from two tropical sites, one in Brazil and one in the Congo. Five different treatments were sampled at each site: monospecific acacia, monospecific eucalypt, below acacias in mixed-species, below eucalypts in mixed-species as well as native vegetation. Po forms and LMWOAs were identified in sodium hydroxide soil extracts using ion chromatography and relationships between these data and available P were determined. At both sites, the concentrations of most Po forms and LMWOAs were different between native ecosystems and monospecific eucalypt and acacia plots. Also, patterns of Po and LMWOAs were clearly separated, with glucose-6-P found mainly under acacia and phytate and oxalate mainly under eucalypt. Despite the strongest changes occurred at site with a higher N2 fixation and root development, acacia introduction was able to change the profile of organic P and LMWOAs in <10 years. The variations between available Pi, Po and LMWOA forms showed that P cycling was dominated by different processes at each site, that are rather physicochemical (via Pi desorption after LMWOAs release) at Itatinga and biological (via organic P mineralization) at Kissoko. Specific patterns of Po and LMWOAs forms found in soil sampled under acacia or eucalypt would therefore explain the effect of acacia introduction in both sites.
Keywords: Brazil; Congo; Ferralsol; Ion chromatography; Mixed-species plantation; P cycling